A prospective study on maternal and perinatal outcome of gestational diabetes mellitus - P. K., Sathiamma; Karunakaran, Lalithambica (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To identify risk factors, study maternal, fetal and perinatal outcome of pregnancy in relation to the glycemic control and different modalities of management in pregnancy complicated by Gestational Diabetes Mellitus (GDM). Methods: Descriptive study conducted in Department of OBG, Government TD Medical College Alappuzha, during the one year period January 2005 to December 2005. Study group comprised of 134 women who are diagnosed to have GDM. The aim was to study the maternal, fetal and perinatal outcome. Results: Despite early diagnosis and treatment the GDM patients in the present study had a statistically significant higher incidence of pregnancy induced hypertension (11.9%) induction of labor about (37.2%), caesarean section (58.96%) preterm delivery (2.99%) macrosomia (2.9%). Incidence of perinatal morbidity was 29.8%, common causes being neonatal hypoglycemia (32.5%), hyperbilirubinemia (12.5%) meconium aspiration syndrome (7.5%). Admission to neonatal unit required in (25%). There were 2 cases of intrauterine deaths, 2 cases of neonatal deaths and no still births. Perinatal mortality was 2.9%. Conclusions: The occurrence of GDM is a high-risk situation. Maternal morbidity, perinatal morbidity and mortality are increased in women with GDM. All pregnant women should be screened for GDM with a 50gm oral glucose load followed by a glucose determination 1 hour later. This helps to detect all GDM cases earlier and so timely intervention can be done which will reduces the complications. Proper management of GDM during the antenatal period will improve pregnancy outcome.